Synopsis of tribe Verbeneae Dumortier (Verbenaceae) in Peru - O’leary, Nataly; Mulgura, Maria Ema (Phytotaxa, 2014)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–> In the present work a revision of tribe Verbeneae for Peru is presented, descriptions and illustrations for each taxa are presented. In this country this tribe is represented by 16 taxa: four Glandularia species, five Junellia species, one Mulguraea species and four Verbena species and two varieties; six of these taxa are endemic to Peru. Three new combinations are presented: Glandularia cuneifolia, Junellia clavata and Verbena glabrata var. hayekii. Nine new synonyms are proposed, lectotypes are designated for Verbena cuneifolia, Verbena clavata and Verbena villifolia, and an epitype is designated for Verbena pogostoma. <!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–><!–[if gte mso 10]> <![endif]–>